Systematic Literature Review: The Relationship between Self-Efficacy and Students' Critical Thinking Skills - Rihadatuj Jihanul Afifah; Martyana Prihaswati; Iswahyudi Joko Suprayitno (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study uses a Systematic Literature Review (SLR) technique with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology through Google Scholar and Web of Scientific Journals Publish or Perish to investigate the relationship between students' critical thinking skills and self-efficacy through a review of 24 publications published between 2018 and 2025 in various journals. Based on the analysis findings, research on critical thinking skills and self-efficacy has been conducted extensively at different levels of education, with the majority (73%) performed in junior high schools. Furthermore, 62% of quantitative research is often used, and this research predominantly develops critical thinking skills. This dominance indicates that self-efficacy is generally considered a supporting variable rather than the primary focus of the topic, thereby opening opportunities for future research on broader subjects and methods.